Challenges and executive requirements of advanced health system governance based on general health policies in Iran: qualitative research - Masoud Aboulhallaj; Seyed Masood Mousavi; Mehdi Jafari; Abbas Vosoogh-Moghaddam; Sajjad Bahariniya; Shabnam Ghasemyani; Sedighe Sadat Tabatabaei Far (BMC, 2024)
Abstract Objective The optimal management of the health system depends on its functions. The functional issues of Iran's health system are organized in a scattered manner and it has many challenges, especially in the field of stewardship. In order to achieve sustainable health-oriented development, bold and smart policy reforms in the main components of the health system are essential. The purpose of this study was to identify challenges and institutional-operational requirements in order to promote stewardship based on the general health policies of the country. Methods This study was conducted qualitatively with a framework analysis approach on policy makers and health experts. Purposive sampling was done with maximum diversity. To achieve a comprehensive view, snowball sampling was completed, resulting in the participation of 47 individuals in this study. A semi-structured interview was used to collect data. The analysis was done in MAXQDA software. Results Challenges and requirements for the implementation of General Health Policy tasks in promoting the function of stewardship, according to the World Health Organization model, in 3 fields of vital evidence production and policymaking (4 main topics and 20 sub-topics), internal governance (6 main topics and 23 subtopics) and Inter-Sectoral Leadership (2 main topics and 6 subtopics) were categorized. The most important challenges in the field of stewardship included fragmentation, the lack of an integrated information system and coherent and coordinated evidence production institutions, and weakness in the supervisory dimension due to the fatness of the structure, conflict of interests, and lack of transparency in responsibilities. Conclusion It seems that the creation of comprehensive governance structures in the form of a network in active interaction with the Secretariat of the Supreme Council of Health and Food Safety, the development of the information system, the coordination of vital evidence production institutions, capacity building to strengthen intra-sectoral governance and inter-sectoral leadership and create a suitable platform be effective for public participation.